Graphene oxide increases the phototransduction efficiency of copolymeric nanoimplants and rescues visual functions in rat and pig models of Retinitis pigmentosa - F. Galluzzi (Nature Communications, 2025)
Abstract Photoreceptor degeneration in Retinitis pigmentosa (RP) is a leading cause of inherited blindness, for which few effective treatments are available. Graphene’s exceptional electrical, optical, and mechanical properties, along with its biocompatibility, make it a promising material for retinal stimulation. Building on prior success with conjugated polymers in rodent RP models, we developed injectable retinal nanoimplants that blend a donor-acceptor polymeric architecture with graphene oxide flakes. Here we show that graphene significantly improved the photovoltaic efficiency and enhanced light-evoked responses in blind retinal explants. In RP-affected Royal College of Surgeons rats, a single subretinal injection of these nanoimplants restored light-driven behaviors and visual brain activity at lower luminances than polymer-only particles without any proinflammatory effects. Moreover, this technology restored retinal activity in a pig model of chemically induced degeneration, demonstrating the valuable translational potential of the injectable nanoplatform in the treatment of retinal degenerative diseases.